Strategi Peningkatkan Partisipasi Masyarakat dalam Pengembangan Madrasah Diniyah di Ponorogo - Rihatul Karimah; Medina Nur Asyifa Purnama; Wiwin Rif’atul Fauziyati (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article aims to determine how to increase community participation strategies in the development of Madrasah Diniyah Fathul Ulum in Kedungbanteng Village, Sukorejo District, Ponorogo Regency. This study method uses a descriptive method, because it is carried out by describing and identifying strategies used to increase community participation in the development of Madrasah Diniyah Fathul Ulum. The results of this study are that strategies to increase community participation include various forms of participation, such as participation in thoughts, energy, and expertise, as well as resource support and roles in planning, implementing, monitoring, and evaluating education programs. The conclusion of this study is that increasing community participation makes a significant contribution to the development of Madrasah Diniyah Fathul Ulum.